Nursing rounds of a patient with coma and edema complicated with tension blister rupture of sacrococcygeal skin (1例神昏水肿合并骶尾皮肤张力性水泡破裂患者的护理查房报告) - ZHENG Naihua (郑乃花); YANG Dongmei (杨冬梅); LI Ye (李野) (Association of Integrative Nursing, 2023)
This paper summarized the nursing experience of a patient with coma and edema complicated with tension blister rupture of sacrococcygeal skin. On the basis of local wound dressing change, a multidisciplinary team had organized the nursing ward rounds to analyze the potential causes of skin problems. According to the concept of holistic nursing, integrated traditional Chinese and western medicine nursing plan had been adopted to improve the healing of skin lesions and improve the patient's quality of life. (本文总结1例神昏水肿患者合并骶尾皮肤张力性水泡破裂的护理经验。局部伤口换药的基础上, 通过组织多学科护理查房, 分析导致患者皮肤问题的成因, 根据整体护理观念, 采用中西医结合护理措施, 促进皮损伤口愈合, 提高了患者生存质量。)